Comorbidities and medications of patients with chronic hepatitis C under specialist care in the UK. Issue 12 (30th August 2017) - Hudson, Benjamin; Walker, Alex J.; Irving, William L.
Abstract : Designing services with the capacity and expertise to meet the needs of the chronic hepatitis C (CHC) population in the era of direct acting antivirals (DAAs), and widening access to such treatments, requires detailed understanding of the characteristics and healthcare needs of the existing patient population. In this retrospective analysis of data from the National HCV Research UK Biobank between March 2012 and October 2014, the characteristics of the CHC population currently under specialist care in the UK were evaluated—with specific focus upon use of medications, adverse lifestyle choices, and comorbidities. Demographic data, risk factors for CHC acquisition, HCV genotype, liver disease status, lifestyle factors, comorbidities, and medication classes were collected. Data were analyzed by history of injecting drug use (IDU), age, and severity of liver disease. A total of 6278 patients (70.5% white; median age, 52 years) from 59 UK specialist centres were included; 59.1% of patients had acquired HCV through IDU. The prevalence of adverse lifestyle factors was significantly lower in non‐IDU compared with previous IDU or recent IDU patients. Depression was common in the previous (50.8%) and recent IDU (68.1%) groups, compared with 27.6% in non‐IDU patients. Cirrhosis was common (23.6%), and prevalence increased with age. We describe a heterogeneous, polymorbid, and aging population of CHC patients in secondary care, and demonstrate underrepresentation of injecting drug users within the current system. The implications of this present significant challenges to physicians and healthcare commissioners in designing services which are fit for purpose inthe DAA era.